Induction of labour in prolonged pregnancy and its outcome (Medicine Today, 2015)
A prospective study was done in the Department of Obstetric and Gynecology, Dhaka Medical College Hospital, Dhaka from the January 2007 to June 2007. For the study 50 patients with uncomplicated prolonged pregnancy admitted during the study period were selected fulfilling the inclusion and the exclusion criteria. The study was conducted to evaluate the outcome of induction in prolonged pregnancy. From this study it was found that routine induction of labour at 41 to 42 weeks may be beneficial rather than continuing the pregnancy to have spontaneous labour which may increase the per perinatal mortality and morbidity. It was also found that due to routine induction of labour in prolonged pregnancy, vaginal delivery rate is more than caesarean section in multigravida than primigravida. Regarding the cause of failure of induction of labour it was found that the main causes are foetal distress and abnormal uterine action. The present study has proved that the use of Prostaglandin for cervical ripening, the delivery outcome can be improved. The study also showed that indiction of labour is not associated with any major intraprtum and postpartum foetal and maternal complication.Medicine Today 2014 Vol.26(2): 100-103